Threshold and Group Size Uncertainty in Common-pool Resources: An Experimental Study. (November 2020) - Kidwai, Abdul H.; de Oliveira, Angela C. M.
Threshold common-pool resources (TCPRs), such as fisheries or groundwater reserves, face irreversible damage if harvesting exceeds a sustainability threshold. Uncertainty about the threshold for sustainable use or the number of resource users can exacerbate the overharvesting problem. Policy makers may therefore seek to reduce threshold or group size uncertainty in TCPRs. Overall, we find that reducing threshold and group size uncertainty (moving from high to low uncertainty) increases expected earnings from the resource. However, complete elimination of group size uncertainty reduces expected earnings. Furthermore, the impact of group size uncertainty on earnings varies by the level of threshold uncertainty. Moving from high to low group size uncertainty increases earnings at low levels of threshold uncertainty but not at high levels of threshold uncertainty. Taken together, we find that reducing threshold uncertainty is beneficial while tackling group size uncertainty requires a more nuanced approach, highlighting the importance of a joint analysis.